Diaphyseal osteomyelitis of femur with suspected ewing sarcoma in 8 years old children: a case report - Sananta, Panji; Rizal, Hidayat (International Journal of Research in Medical Sciences, 2018)
Metaphyseal osteomyelitis in children due to direct bone trauma or vascular insufficiency is a frequent problem in orthopaedic surgery. In contrast, diaphyseal osteomyelitis represents a rare entity that almost exclusively affects child with bony infarct in sickle cell anemia. Differentiating neoplasm from musculoskeletal infection can sometimes be very challenging. In particular, Ewing sarcoma can masquerade as osteomyelitis with the presenting symptoms of fever, localized bone pain, and elevated inflammatory markers common to both entities, although osteomyelitis is a totally different type of disease. In this article, we report the case of chronic osteomyelitis of the femur in an immunocompetent and otherwise healthy 8 years old boy with minor inflammation signs and misleading clinical features. The X-ray showed onion skin periosteal reaction. We evacuated about 200 cc of abscess. Biopsy report revealed polimononuclear, mononuclear, and necrotic inflammatory cells. The patient was treated with antibiotic for two weeks and discharged with improved general condition. Six months follow-up shows clinical and radiological improvement. The diagnosis had to be confirmed by surgery which allowed the initiation of a targeted therapy. A case of diaphyseal osteomyelitis of a femur, lacking predisposing factors or trauma, is unique in children and never been reported previously.